Masochistic Performance of Scheherazade: A Multimodal Analysis of Prince Charming - Attiya Zafar; Nadia Anwar (CINEJ Cinema Journal)
This study attempts to highlight the embedded masochist aesthetics supporting the masochistic patterns in a Pakistani short film Prince Charming (2021), directed by Sheheryar Munawar Siddiqui, a Pakistani actor, film producer, director and television host. The focus remains on female protagonist, Scheherazade’s performative masochistic proclivities in an unsatisfactory marital relationship. This research takes Freud’s notion of repetitive compulsion as its referential point that triggers masochism and identifies Scheherazade’s urges and desires. Though masochism is about gaining the pleasure while bearing the pain, in the case of the film the pain is self-inflicted in the form of silence, inexpressibility, self-talks and romantic void between Scheherazade and her husband Akbar. This research offers a stand point to comprehend the subliminal threads of visual masochism which are apparently hidden in the film but are the prospective hooks to elaborate the psychological suffering of the character. The research propagates the idea that masochist aesthetics are nevertheless the stepping stone for pointing out the masochist self of Scheherazade, well exhibited through her performance.